Interaction of Absorptive Capacity and Entrepreneurial Orientation on Firm’s Profitability - Heikkilä, Vili (My University, 2015)
As the competitiveness on markets increases, the role of innovation grows more important for firm’s success and profitability. The importance of innovativeness in organizations is well noted, and companies are paying increasing attention to their innovation processes. However, the innovation processes are complex and difficult to controll. This paper aims to shed light on companies’ innovation and product development processes, to help organizations to improve their processes to increase the profitability of their innovations. Even though numerous scholars have acknowledged the role of entrepreneurial orientation and absorptive capacity on organization’s innovation processes, still the existing research on the interplay between the two is limited. This thesis aims to improve our understanding on the effects of interplay between absorptive capacity and entrepreneurial orientation on firm profitability. The thesis examines the existing literature on performance effects of each of the constructs, individually and as interplay, to create a holistic understanding of the phenomenon. This is followed by empirical study on Finnish food industry utilizing mixed method combining cluster analysis and qualitative within-case and cross-case analyses. The results of the study revealed five common practices and processes among the case companies such as (1) appreciation of rich customer interaction, (2) agile external knowledge processing (3) informal daily dialogues (4) experimental product development (5) cost- and customer value driven opportunity capture.
Keywords: Entrepreneurial orientation; Absorptive capacity; Interplay; Profitability; Innovation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|